Hydrilla Integrated Management - Jennifer L. Gillett-Kaufman; Verena-Ulrike Lietze; Emma N.I. Weeks (EDIS)
The focus of the book is on hydrilla management in Florida, although the described tactics are known and used in many of the 28 states in the United States with hydrilla infestations. Divided in seven chapters, the book guides the reader through a general introduction to the problems associated with hydrilla; identification of the plant; instructions for early detection of infestations including federal and state laws and regulations; detailed descriptions of available control tactics; proposals for integrated management plans; descriptions of insects and fish associated with hydrilla; and supplementary information including contacts for assistance when readers encounter infestations. This 144-page book was written by Jennifer L. Gillett-Kaufman, Verena-Ulrike Lietze, and Emma N.I. Weeks, and published by the UF Department of Entomology and Nematology, August 2014.